Antibody in Lymphocyte Supernatant (ALS) responses after oral vaccination with live Shigella sonnei vaccine candidates WRSs2 and WRSs3 and correlation with serum antibodies, ASCs, fecal IgA and shedding. - Malabi M Venkatesan (Public Library of Science (PLoS), 2021)
The levels of antigen-specific Antibodies in Lymphocyte Supernatant (ALS) using an ELISA are being used to evaluate mucosal immune responses as an alternate to measuring the number of Antibody Secreting Cells (ASCs) using an ELISpot assay. A recently completed trial of two novel S. sonnei live oral vaccine candidates WRSs2 and WRSs3 established that both candidates were safe, well tolerated and immunogenic in a vaccine dose-dependent manner. Previously, mucosal immune responses were measured by assaying IgA- and IgG-ASC in peripheral blood mononuclear cells (PBMCs). In this report, the magnitude of the S. sonnei antigen-specific IgA- and IgG-ALS responses was measured and correlated with previously described ASCs, serum antibodies, fecal IgA and vaccine shedding. Overall, the magnitude of S. sonnei anti-Invaplex50 ALS was higher than that of LPS or IpaB, and both vaccines demonstrated a more robust IgA-ALS response than IgG; however, compared to WRSs3, the magnitude and percentage of responders were higher among WRSs2 recipients for IgA- or IgG-ALS. All WRSs2 vaccinees at the two highest doses responded for LPS and Invaplex50-specific IgA-ALS and 63-100% for WRSs3 vaccinees responded. Regardless of the vaccine candidate, vaccine dose or detecting antigen, the kinetics of ALS responses were similar peaking on days 7 to 9 and returning to baseline by day 14. The ALS responses were vaccine-specific since no responses were detected among placebo recipients at any time. A strong correlation and agreement between responders/non-responders were noted between ALS and other mucosal (ASC and fecal IgA) and systemic (serum antibody) immune responses. These data indicate that the ALS assay can be a useful tool to evaluate mucosal responses to oral vaccination, an observation noted with trials of other bacterial diarrheal pathogens. Furthermore, this data will guide the list of immunological assays to be conducted for efficacy trials in different populations. It is hoped that an antigen-specific-ALS titer may be a key mucosal correlate of protection, a feature not currently available for any Shigella vaccines candidates. https://clinicaltrials.gov/show/NCT01336699.